Enhanced proton conductivity of Nafionazolebisphosphonate membranes for PEM fuel cells - Teixeira, António P. S. (2020)
Fuel cells are among the cleaner alternatives of sustainable energy technologies, where their protón exchange membranes continue to be a key component with many challenges and opportunities ahead. In this study, diﬀerent indazole- and benzotriazolebisphosphonic acids were prepared and incorporated into new Nafion-doped membranes up to a 5 wt% loading. The new membranes were characterised, and their proton conductivities were evaluated using electrochemical impedance spectroscopy. Membranes with a 1 wt% loading showed better proton conductivities than Nafion N-115 at all temperature and under relative humidity conditions studied. In these conditions, the best value was observed for the membrane doped with [hydroxy(1H-indazol-3-yl)methanediyl]bis(phosphonic acid) (BP2), with a proton conductivity of 98 mS cm-1. Activation energy (Ea) values suggests that both Grotthuss and vehicular mechanisms are involved in the proton conduction across the membrane.